Guillain-Barré syndrome after brachial plexus trauma: case report Síndrome de Guillain-Barré após traumatismo de plexo braquial: relato de caso - Marcos R.G. de Freitas; Osvaldo J.M. Nascimento; Maria Beatriz B.P. Harouche; Adolfo Vasconcelos; Heloy Darroz Jr; Tânia Maria Escada (Arquivos de Neuro-Psiquiatria)
The Guilllain-Barré syndrome (GBS) is an acute predominantly demyelinating polyneuropathy. In many cases GBS is preceding by infection, immunization, surgery or trauma. Although there are a few reports of GBS after head trauma, there is no report of this syndrome after brachial plexus injury. We report on a 51 years-old man who presented GBS fifteen days after a brachial plexus trauma. The polineuropathy resolved completely in a few weeks. We believe that GBS was triggered by the trauma that evoked an immune mediated disorder producing inflammation and demyelination of the peripheral nerves. A síndrome de Guillain-Barré (SGB) é uma polineuropatia predominantemente desmielinizante, que ocorre na maioria das vezes após uma infecção, vacinação, cirurgia ou traumatismo. Embora tenham sido descritos alguns casos após traumatismo crânio encefálico, ainda não foi referido caso de SGB após traumatismo do plexo braquial. Relatamos o caso de um homem de 51 anos que 15 dias após ter apresentado paralisia traumática do plexo braquial, desenvolveu SGB. Recuperou-se inteiramente em algumas semanas. Achamos que em nosso caso a SGB foi desencadeada pelo traumatismo, que provocou distúrbios imunológicos com conseqüente acometimento dos nervos periféricos.